Direct-Acting Oral Anticoagulant Dabigatran as a Bridging Therapy while Optimizing Warfarin Dosage for Cardioembolic Stroke - Narayanaswamy Venketasubramanian; Yohanna Kusuma; Leonard Leong Litt Yeo; Bernard Chan (Cerebrovascular Diseases Extra)
Introduction: Parenteral heparin is widely used as bridging therapy while optimizing oral anticoagulation (OAC). Newer direct-acting OACs (DOACs) attain therapeutic effect very quickly. We report the use of dabigatran as bridging therapy during warfarin optimization for cardioembolic stroke in two patients who opted to receive warfarin for long-term anticoagulation for secondary stroke prevention. Case Presentations: Patient A was a 60-year-old man with hypertension, hyperlipidaemia, and gout who was admitted with a sudden onset of left-sided weakness. Clinically, he was alert but had right gaze preference and left-sided hemiplegia. The clinical diagnosis was of a right cortical stroke. He underwent intravenous tPA augmented with sonothrombolysis – the National Institute of Health Stroke Scale (NIHSS) score fell from 7 to 0. Repeat brain scan showed infarcts in the right frontal and parietal lobes. He was found to have atrial fibrillation (AF) and advised anticoagulation. He opted for warfarin with dabigatran bridging which was started on day 2 of his hospital admission. His International Normalized Ratio (INR) exceeded 2 by day 6 of anticoagulation, at which time the bridging dabigatran was stopped, fixed-dose warfarin was continued, and he was discharged well. On subsequent reviews in the clinic, his INR was in the therapeutic range of 2.0–3.0. He had no bleeding or recurrent ischaemic events during follow-up. Patient B was a 78-year-old man with a hypertension, hyperlipidaemia, and diabetes mellitus. He was admitted after he developed difficulty talking and mild right-sided weakness. Clinically, he was alert but had expressive aphasia and mild right-sided upper limb weakness (NIHSS 6). The clinical diagnosis was of a left cortical stroke. The brain scan showed a left posterior frontal and parietal infarct. He was out of the time window for recanalization therapy and was treated conservatively. He was found to have AF and advised anticoagulation. He opted for warfarin with dabigatran bridging which was started on day 1 of his hospital admission. His INR was almost 2 by day 5 of anticoagulation, at which time the bridging dabigatran was stopped and fixed-dose warfarin continued. He declined daily blood taking – his INR 4 days later was in the therapeutic range of 2.0–3.0. He had no bleeding or recurrent ischaemic events. He underwent rehabilitation uneventfully and was discharged well. Conclusions: The use of DOACs such as dabigatran as bridging therapy during optimization of OAC is feasible. Compared to heparin as bridging therapy, DOAC has the advantage of oral administration, lower cost, and possibly lower bleeding risks. This novel practice may be applicable in thrombosis in arterial and venous circulations, e.g., ischaemic stroke, deep venous thrombosis, pulmonary embolism.